Review, Testing and Validation of Capacity and Delay Models at Unsignalized Intersections - Cvitanić, Dražen; Breški, Deana; Vidak, Boris (Promet - Traffic&Transportation, 2007)
This paper deals with problems related to the capacity anddelay models at unsignalized intersections. The parameters ofvarious models are calibrated based on the on-site data obtainedin the countries where the models were developed. Thispaper deals with two problems: The first is the reliability of appliedmethodology in general, and the second is the acceptabilityof model parameters for the use in prevailing road and trafficconditions in Croatia.The first section presents the background review of the gapacceptance theory which is the basis for the development of thecapacity and delay models. The mathematical derivation of thebasic capacity models is presented as well as the resulting capacitymodels according to the assumed theoretical distributionof head ways in the priority stream. This paper also presents themethods for the calculation of the capacity considering the existenceof traffic streams of different hierarchies. The results ofvmious theoretical capacity models testing are presented. Thesecond section presents a review of queuing theory and the resultingstationary and time-dependent delay models. The underlyinghypothesis as well as reliability and limitations of thedelay models are presented. Also, the Highway capacity manualdelay model was tested against field data.